2023
DOI: 10.3390/buildings13040905
|View full text |Cite
|
Sign up to set email alerts
|

Productivity Analysis and Associated Risks in Steel Structures

Abstract: Construction can be analyzed at industry, firm, project, and activity/task levels. Given that there are differences between the concepts of productivity and uses of productivity data, depending on the level of analysis, there is no single meaning of construction productivity, except of an output/input ratio. Furthermore, there is little knowledge in the extant literature about steel structure productivity, sustainability, and risks. Moreover, through the investigation of the grey literature, i.e., the national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The assembly of large metal structures is a complex process that requires careful planning, coordination, and the use of specialized methods and tools [24]. In addition to the aforementioned stages, two crucial steps in the production process of large metal structures are component layout and component joining.…”
Section: Assemblymentioning
confidence: 99%
“…The assembly of large metal structures is a complex process that requires careful planning, coordination, and the use of specialized methods and tools [24]. In addition to the aforementioned stages, two crucial steps in the production process of large metal structures are component layout and component joining.…”
Section: Assemblymentioning
confidence: 99%
“…Productivity and risk are related; a previous study showed that the more the productivity of steel structure work increases, the greater the risk to itself [7]. This productivity depends on many factors, i.e., the height of construction, high wind, skills and experience, job site planning, and training activities [8].…”
Section: Introductionmentioning
confidence: 99%